Haematological cancers: improving outcomes. A summary of updated NICE service guidance in relation to Specialist Integrated Haematological Malignancy Diagnostic Services (SIHMDS). Issue 6 (7th April 2017) - Snowden, John A; O'Connell, Susan; Hawkins, James; Dalley, Chris; Jack, Andrew; Mannari, Deepak; McNamara, Chris; Scott, Mike; Shenton, Geoff; Soilleux, Elizabeth; Macbeth, Fergus
Abstract : Haematological malignancies are a diverse group of cancers that affect the blood, bone marrow and lymphatic systems. Laboratory diagnosis of haematological malignancies is dependent on combining several technologies, including morphology, immunophenotyping, cytogenetics and molecular genetics correlated clinical details and classification according to the current WHO guidelines. The concept of the Specialised Integrated Haematological Malignancy Diagnostic Services (SIHMDS) has evolved since the UK National Institute for Health and Care Excellence (NICE) Improving Outcomes Guidance (IOG) in 2003 and subsequently various models of delivery have been established. As part of the 2016 update to the NICE IOG, these models were systematically evaluated and recommendations produced to form the basis for quality standards for future development of SIHMDS. We provide a summary of the systematic review and recommendations. Although the recommendations pertain to the UK National Health Service (NHS), they have relevance to the modern delivery of diagnostic services internationally.